Translation Procedures of Economic Article from English into Indonesian - Yeni Noryatin; Inta Masni Sinaga; Winda Lutfiyanti; Esterria Romauli (Jurnal Bahasa Asing, 2022)
This research aims to analyze the translation procedures of economic articles from English into Indonesian by the fourth semester students 2020/2021 in STBA JIA. The data will be analyzed by the theory of Vinay and Darbelnet about translation procedures. This research is qualitative research with descriptive analysis, which gives more attention on how deep the translation’s knowledge towards the concept which was being learned and how the theory is used to translate the article. The data of the research is the final test of translation class which economic articles become the data source that are translated by the student. The result of the analysis shows that some procedures are used by students to get the acceptable meaning in Indonesian language. From the analysis, it is found that basically all the students gradually can translate well after having many translation practices.